Piezoresponse behavior of niobium doped bismuth ferrite thin films grown by chemical method - Simões, Alexandre Zirpoli [UNESP]; Garcia, Filiberto Gonzalez; Riccardi, C. S. [UNESP] (Elsevier B.V. Sa, 2010)
This paper focuses on the piezoresponse characteristics at room temperature in niobium modified bismuth ferrite thin films (BFN) deposited on Pt/TiO(2)/SiO(2)/Si (1 0 0) substrates by the soft chemical method. The obtained films were grown at a temperature of 500 degrees C. The Nb dopant is effective in improving electrical properties of BFO films. XPS results show a single-phase Nb-doped BFO thin films with a Fe(3+) valence state. It was found that Nb-doped BFO thin films exhibited good electrical properties, such as improved capacitance-voltage and high piezoeletric coefficient, indicating a promising material for use in future memories based on magnetic ferroelectrics. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ferroelectrics; Thin films; Chemical synthesis; Piezoelectricity